Evaluation of the Physical Fitness of 5th Grade Students at Public Elementary Schools in Pabelan Magelang using TKSI - Muhammad Nasrodin; Aris Fajar Pambudi (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to determine the level of physical fitness among 5th grade students at public elementary schools in the Pabelan subdistrict, Magelang using the Indonesian Student Fitness Test (TKSI). This study employs a quantitative approach with a descriptive analysis design. The population in this study consists of all 5th grade students at public elementary schools in the Pabelan sub-district, specifically Pabelan 2 Public Elementary School and Pabelan 3 Public Elementary School, using total sampling. Data collection was conducted through field-based testing based on the TKSI Phase C instrument, which covers the components of coordination, accuracy, agility, muscle strength, and cardiorespiratory endurance. Data were analyzed using SPSS version 27 for Windows. The results of the study indicate that the overall level of physical fitness among students falls into the “Fair” category, with the following breakdown: 0% in the “Excellent” category, 16% in the “Good” category, 44% in the “Fair” category, 25% in the “Poor” category, and 15% in the “Very Poor” category. Based on gender, male students were in the “Fair” category with the highest percentage at 50%, while female students were in the “Poor” category with the highest percentage at 39%. These results indicate that students’ physical fitness is not yet optimal, necessitating a focus on targeted and sustained increases in physical activity.